2020
DOI: 10.1098/rsos.200233
|View full text |Cite
|
Sign up to set email alerts
|

Differences between and within individuals, and subprocesses of face cognition: implications for theory, research and personnel selection

Abstract: Recent investigations of individual differences have demonstrated striking variability in performance both within the same subprocess in face cognition (e.g. face perception), but also between two different subprocesses (i.e. face perception versus face recognition ) that are assessed using different tasks (face matching versus face memory ). Such differences between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 65 publications
7
49
0
Order By: Relevance
“…SRs who participated in this study were recruited from a larger cohort of recently reported SR individuals (Ramon, 2021). In short, they were identified as disposing of exceptional face processing ability if they achieved high performance (among the top 5% of previously tested normative samples; Stacchi et al, 2020;Fysh et al, 2020) on at least two of three challenging tests of face cognition: the YBT (long form; Stacchi et al, 2020;Fysh et al, 2020;Bruck et al, 1991), the FICST (Stacchi et al, 2020;Fysh et al, 2020;Jenkins, White, Van Montfort & Burton, 2011), and the CFMT+ (Russell et al, 2009). SR status was conferred only for those whose performance exceeded the 95% CI for typical performance on at least two of the three.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…SRs who participated in this study were recruited from a larger cohort of recently reported SR individuals (Ramon, 2021). In short, they were identified as disposing of exceptional face processing ability if they achieved high performance (among the top 5% of previously tested normative samples; Stacchi et al, 2020;Fysh et al, 2020) on at least two of three challenging tests of face cognition: the YBT (long form; Stacchi et al, 2020;Fysh et al, 2020;Bruck et al, 1991), the FICST (Stacchi et al, 2020;Fysh et al, 2020;Jenkins, White, Van Montfort & Burton, 2011), and the CFMT+ (Russell et al, 2009). SR status was conferred only for those whose performance exceeded the 95% CI for typical performance on at least two of the three.…”
Section: Methodsmentioning
confidence: 99%
“…Ability in matching images of unfamiliar face identities varies widely between neurotypical adults (Fox & Bindeman, 2020;Estudillo & Bindemann, 2014;Fysh & Bindemann, 2017;Stacchi et al, 2020;Fysh et al, 2020). At the upper end of this spectrum are Super-Recognizers (SRs), originally reported by Russel, Duchaine and Nakayama (2009) as possessing exceptional facial identity processing capabilities across a range of subprocesses, including face matching, recognition, and identification.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ability in matching images of unfamiliar face identities varies widely between neurotypical adults 1 5 . At the upper end of this spectrum are super-recognizers (SRs), originally reported by Russell et al 6 as possessing exceptional facial identity processing capabilities across a range of sub-processes, including face matching, recognition, and identification.…”
Section: Introductionmentioning
confidence: 99%